THE THERAPEUTIC AND TOXICOLOGICAL EFFECT OF CHITRAK (PLUMBAGO ZEYLANICA L.)- A REVIEW (AYUSHDHARA, 2015)
Chitraka based Ayurvedic medicines are commonly used by Ayurvedic physicians. Chitraka is toxic in nature even then it is used as a medicine after Shodana (purification) and in therapeutic dose. Shodhana procedure is not only represent a process of purification, but also in addition to a process of detoxification and the ultimate objective of Shodhana is to enhance the biological efficacy of the drug. In therapeutic doses it has capacity to treat many diseases. Traditionally P. zeylanica is used as a stimulant, digestive, expectorant, laxative, abortifacient, antiperiodic and in the treatment of muscular pain, intestinal parasites, anemia, dysentery, fever or malaria and rheumatic diseases. P. zeylanica contains a variety of important chemical compounds. Different parts of the plant possess naphthaquinones, alkaloids, glycosides, steroids, triterpenoids, tannins, phenolic compounds, flavanoids, saponins, coumarins, carbohydrates, fixed oil and fats and proteins. Its fruits contains plumbagin, glucopyranoside and sitosterol. There are so many researches has been done on this plant like Anti-carcinogenic activity, Anti-diabetic, wound healing, contraceptive effect, Hepato-protective, Anti-microbial, Anti-inflammatory and Anthelmintic. This review gives us opportunity to understand the toxic effects, medicinal importance, biological activities and pharmacological effects of Plumbago zeylanica. This article gives an overview of medicinal uses and poisonous properties of Chitraka.